Measurements of turbulent boundary layer growth over a longitudinally curved surface - Meroney, Robert N., author; Fluid Dynamics and Diffusion Laboratory, Department of Civil Engineering, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1974)
The result of an "additional rate of strain" on a turbulent parcel of fluid as it undergoes even mild streamline curvature can be very large. Yet until recently skin friction and heat transfer calculations have ignored this effect. Recent measurements over turbine cascades suggest curvature influences heat transfer by an order of magnitude. In addition there exists a strong analogy between the effects of centrifugal body forces and the buoyancy body force arising in density stratified flow in a gravity field. This note reports the results of a set of measurements of boundary layer development over convex and concave surfaces and compares the results with various turbulence models utilized in computational programs. A moderate curvature wind tunnel test section was constructed (δ/R = .01 to .02) to examine the influence of curvature on boundary layer structure. The boundary layer rate of growth, compared to that of a boundary layer in the same pressure gradient on a flat surface, was decreased on the convex surface and increased on the concave surface by ten to twelve percent as a result of only an apparent one to two percent perturbation on the size of the source terms in the Reynolds stress equations. Measurements are available of longitudinal static wall pressure, vertical stagnation pressure and single and cross-wire anemometer voltages at a sequence of five downstream stations. Lateral traverses at six heights for two downstream stations were completed over the concave side. Analog and digital interpretation of anemometer signals provided data of u, v, u'2, v'2, u'v', u'v'2 u'2v', u'3, and v'3.
CER73-74RNM26.
Prepared under Office of Naval Research - NR 062-414/6-6-68 (Code 438).
I. C. Aero Tech. Note 74 - Jan. 1974.
January 1974.
Keywords: Fluid mechanics; Laminar flow; Vortex-motion; Boundary layer